THE ISLAMIC INFLUENCE ON BUILT ENVIROMENT IN ANCIENT ISLAMIC CITIES: A DESCRIPTIVE-ANALYTIC STUDY - Shehada, Ziad M. M. (Journal of Al-Tamaddun, 2020)
Built environment is considered to be the ‘physical face’ of a civilization. Accordingly, scientists studying an ancient civilization often refer to the remains of a civilization’s-built heritage in order to better understand its cultural system. This has been evident in ancient Islamic cities such as Baghdad, Al-Medina, Fez, Kairouan, Marrakech, and Granada, as these cities have been well-framed, both legally and systematically. This Islamic frame is referred to as the Islamic Fiqh, and it has been accompanied by developments in urban Islamic communities. This research aims to examine the impact of Fiqh Al-Maliki on the built environment, and the possibility of investing Fiqh to establish tourist guidance based on scientific interpretation derived from legal and cultural systems. The researcher adopted a descriptive-analytic methodology to analyze the Fuqaha’ opinions, as well as to understand the relationship between Islamic architecture and Islamic Fiqh. It was found that Fiqh Al-Maliki contributed toward the formation of Islamic cities through the framed legal system. This Fiqh and historic wealth can be beneficial to realize the first image of the built environment and maintain its original form.